Impact of Land Use and Climate Changes on Flood Inundation Areas in the Lower Cimanuk Watershed, West Java Province - Muhammad Ardiansyah; Rifqi Aditya Nugraha; La Ode Syamsul Iman; Syamsu Dwi Djatmiko (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Land use and climatic changes potentially affect the surface runoff and inundation in watershed zones. Every year, the outflow of the Cimanuk River causes floods across the majority of the upper area of the Cimanuk Watershed, as well as the lower area. This study aimed to assess the impact of climatic and land use changes on future flood inundation in the Lower Cimanuk Watershed using a RRI model. Land-use change has been prepared by modeling using a multi-layer perceptron neural network and Markov Chain approach, while climate change using HadGEM2-ES global climate model data under scenarios RCP4.5. In particular, the forest area was projected to decline in this watershed zone, from 19.54% of the total area in 2019 to 17.73% in 2050. Similarly, the area of paddy fields was predicted to decline from approximately 34.36% in 2019 to 29.65% in 2050. In contrast, other types of land use such as dryland agriculture, mixed dryland agriculture, and settlements were projected to increase in the future. The coverage of the simulated flood inundation area using the Rainfall-Runoff Inundation model estimated to reach 179.4 km2 in 2019. The simulation results showed an increase in flood inundation areas in 2030 and 2050, alongside changes in land use and climate. The areas affected by flood inundation were estimated to reach 253.3 km2in 2030. This coverage was expected to increase by 311.9 km2 in 2050, with severely affected land uses including settlements, dry land agriculture, mixed dry land agriculture, paddy fields, and ponds.